2001
DOI: 10.1055/s-2001-11509
|View full text |Cite
|
Sign up to set email alerts
|

Cnidicin, a Coumarin, from the Root of Angelica koreana, Inhibits the Degranulation of Mast Cell and the NO Generation in RAW 264.7 Cells

Abstract: Cnidicin (1) and five related coumarins were isolated from the root extract of Angelica koreana (Umbelliferae) as active principles responsible for the inhibitory effect on the degranulation process of cultured mast cells. Cnidicin (1) demonstrated a significant inhibition upon the release of beta-hexosaminidase from the cultured RBL-2H3 cells in a dose dependent manner (IC50 value, 25 microM) and upon the nitric oxide production from the activated RAW264.7 cells (IC50 value, 7.5 microM). In agreement with thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…6. Each compound was identified by direct comparison of spectral properties, MS, 1 H-NMR and 13 C-NMR with those of the authentic compounds in the literature (Ryu et al, 2001). tumor cell lines, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…6. Each compound was identified by direct comparison of spectral properties, MS, 1 H-NMR and 13 C-NMR with those of the authentic compounds in the literature (Ryu et al, 2001). tumor cell lines, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Coumarin derivatives occur in various spice plants, and have been reported to have antitumoral, 15) fungicidal 16) and anti-inflammatory 17) activities. Although Ryu et al 18) have reported that cnidicin, a coumarin derivative, inhibited mast cell degranulation, degranulation inhibiting activity of 7-methoxycoumarin has not previously been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Their structures were identified by comparison of optical rotations, 1 H-and 13 C-NMR, DEPT, and MS data with the reported ones of the corresponding compounds. 13,[17][18][19][20][21] Among the purified compounds, 3 showed the strongest protective effect against lethality induced by LPS/D-GalN ( Table 2). Pretreatment of mice with 3 at doses of 3, 10, and 30 mg/kg increased survival rates to 40%, 80%, and 100%, respectively, compared with 20% in the control experiment, while pretreatment with dexamethasone as a positive control at doses of 3, 10, and 30 mg/kg increased survival rates to 60%, 100%, and 100%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…10 (1.97 g), and Fr. 11 (3 g 17,20,21) respectively. The structures of the four compounds are shown in Fig.…”
Section: General Proceduresmentioning
confidence: 99%